Delayed response of net primary productivity with climate change in the Yiluo River basin - Tian, Zihao; Qin, Tianling; Wang, Huiliang; Li, Yizhe; Yan, Sheng; Hou, Jun; Li, Chenhao; Abebe, Sintayehu A. (Frontiers in Earth Science, 2023)
Climatic factors are main driver which make net primary productivity have change. In order to study the response of vegetation Net Primary Production to climate factors in the middle reaches of The Yellow River, we choose the Yiluo river basin as the research object. The temporal and spatial distribution of Net Primary Productive of vegetation and the trend change of Slope in the basin from 2000 to 2020 is analyzed. In addition, the correlation between net primary productivity of vegetation and climatic factors (precipitation, temperature) and the time-lag effect were also analyzed. The results show that: 1. The annual average net primary productivity of vegetation in the basin is 556.36gC·m-2 ·a-1, the maximum value occurred in 2019. Most of the NPP of forest vegetation in the basin appeared abrupt points in 2004, while the NPP of cultivated land vegetation in the basin mostly appeared in 2008 and 2009. 2. The result of slope trend analysis of NPP from 2000 to 2020 shows that the NPP in 67.88% of the basin shows a significant increase trend, and the proportion of the area in 3.84% shows a significant decrease, and the other has no significant change. 3. The correlation analysis between NPP and climatic factors shows that there is a positive correlation between precipitation and NPP in 62.37% of the region, and a positive correlation between air temperature and NPP in 62.53% of the region. The mean lag time of NPP responses to precipitation in the basin is 3.4 days, while the mean lag time to temperature responses is 0.7 days. This study is beneficial to understand the influence of climatic factor changes on vegetation activities in the Yiluo River Basin over the years and to effectively deal with the ecological problems of the Loess Plateau in the middle reaches of the Yellow River Basin.